The Influence of Financial Literacy and Pocket Money on the Saving Behavior of SMK Gotong Royong Students - Yuyun Rasai; Sahrul Hi. Posi; Suharli Manoma; Nasrula Kaiyeli (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
This study aims to determine the simultaneous and partial influence of financial literacy and pocket money on students' saving behavior. This study is a type of inferential statistical research conducted to test hypotheses. This study uses secondary data sourced from questionnaires distributed to 66 students. The sampling technique uses Non-Probability Sampling with Convenience Sampling techniques. The analysis method used is multiple linear regression analysis. Based on the results of partial hypothesis testing, it is known that the variables of financial literacy and pocket money have a positive effect on students' saving behavior. While simultaneously, the variables of financial literacy and pocket money have a simultaneous effect on students' saving behavior. The results of the coefficient of determination test obtained an R-square value of 0.721 or 72.1% of students' saving behavior is influenced by financial literacy and pocket money factors, while the remaining 27.9% (100% - 72.1%) is influenced by other factors not explained in this study.